1993
DOI: 10.2135/cropsci1993.0011183x003300010003x
|View full text |Cite
|
Sign up to set email alerts
|

Light Intensity, Row Spacing, and Photoperiod Effects on Expression of Brachytic Stem in Soybean

Abstract: Brachytic stem trait in soybean [Glycine max (L.) Merr] is characterized by a geniculate internode arrangement and markedly shortened internodes; brachytic plants are much shorter than their nonbrachytic isolines. When the brachytic trait expression is suppressed, plants have heights similar to those of their nonbrachytic isolines. A series of greenhouse and field experiments involving light intensity and photoperiod treatments were conducted to determine their effects on plant height and other stem traits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The seeds with brown seed coat germinated earlier than the dark-black, which suggests easier water penetration by the former and required no pretreatment of seeds. Germination of seeds and vegetative growth of the continuous light experiment shows that some seeds were light sensitive which is in agreement with the reports of Akhteret et al (2009), Singh (1997, and Huang et al (1993) while some are not light sensitive (Khan and Rizvi, 1994). The sensitive of seeds observed in trees C, I and V in the illuminated germination studies have their seed germination higher than that of the daylight germination studies at 3WAP.…”
Section: Materials Usedsupporting
confidence: 90%
“…The seeds with brown seed coat germinated earlier than the dark-black, which suggests easier water penetration by the former and required no pretreatment of seeds. Germination of seeds and vegetative growth of the continuous light experiment shows that some seeds were light sensitive which is in agreement with the reports of Akhteret et al (2009), Singh (1997, and Huang et al (1993) while some are not light sensitive (Khan and Rizvi, 1994). The sensitive of seeds observed in trees C, I and V in the illuminated germination studies have their seed germination higher than that of the daylight germination studies at 3WAP.…”
Section: Materials Usedsupporting
confidence: 90%
“…A linear relationship between percent light interception and dry matter increase per day was positively correlated (Shibles and Weber, 1965). Canopy development and light interception may be affected by the morphological traits of a soybean cultivar; however, increased yield was not always reported (Huang et al, 1993; Wells et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Interaction between a weed and crop species is complex and difficult to predict. Differences in cultivar photosynthetic rates (Johnston et al, 1969), leaf orientation (Blad and Baker, 1972), nodulation (Hunt et al, 1990), and morphology (Huang et al, 1993) have been reported and often result in differential light interception. These differences may alter the competitiveness of soybean with weeds.…”
mentioning
confidence: 99%
“…Secondly, shortened internodes suppressed the geotropic straightening that normally would reorient the tilted shoot apex. A recent study indicated that light is a regulatory factor in the brachytic stem development (Huang et al, 1993). Shade treatment inhibited the geniculate expression, whereas increasing photoperiod from 14 to 16 h in the greenhouse decreased the plant height and enhanced the expression of the brachytic stem trait.…”
mentioning
confidence: 99%
“…Lodging is a major limitation to soybean yield, especially in highly productive environments (Cooper, 1971a,b;Leffel, 1961;Noor and Caviness, 1980). Due to its effect on plant height, the brachytic stem character in soybean was suggested as a trait to control lodging (Kilen, 1977;Walker and Boerma, 1978), because it does not substantially reduce fruiting node number or leaf area (Huang et al, 1993).…”
mentioning
confidence: 99%